IMPROVING THE INVESTMENT ENVIRONMENT TO INCREASE THE VOLUME OF INVESTMENT FROM FOREIGN COUNTRIES - Jo’rayev Og’abek (Journal Park Publishing, 2023)
This article is about the ways of effective use of investments in the development of the economy of Uzbekistan, the economic meaning of the concept of investment, factors affecting the volume of investment, sources of investment financing, improving the investment environment in Uzbekistan, creating a favorable business environment, socio-economic reforms aimed at attracting investments, measures to organize the effective use of investments in economic sectors and prospects for attracting investments, directions for the development of economic sectors and industries through the effective use of investments, the impact of investments on the economy, among the population the role of investments in the development of entrepreneurship, along with investment, directions for the introduction of new technologies, advanced experiences, and highly qualified specialists to various industries and sectors, regions, directions for the effectiveness of investments in the development of the economy of Uzbekistan are presented.
Keywords: improving the investment, investment, economy of uzbekistan, active attraction of foreign, action strategy.